Bond compression bulk modulus of the binary tellurite glass - Mohamed Kamari, Halimah; Ab Aziz, Sidek; Wan Yusoff, Wan Mohamad Daud; Hassan, Zainul Abidin; Talib, Zainal Abidin (Universiti Putra Malaysia Press, 2005)
A series of binary tellurite glass (TeO2)x(B2O3)1-x with x= 0.6-0.8 have been calculated using the bond compression model. The atomic ring size of the network has been obtained from the ring deformation model. The composition dependence of these parameters showed the elasticity and hence the respond of this glass system is influence by the chemical nature of tellurite dioxide composition. Variation of the estimated atomic ring size with ratio of the bond compression model Kbc to experimental Ke bulk modulus was studied to obtain more information about the structure of the glass. The result showed that the small value or the large value of Kbc/Ke are attributed to the very close (small ringed) three-dimensional network of these glasses.